GASTRODIPLOMASI THAILAND TERHADAP INDONESIA DALAM MENINGKATKAN CITRA WISATA MELALUI KITCHEN OF THE WORLD - Tika, Anisya; Fuadi, Ahmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Thailand is known as a country that is strong in sex tourism. To change the image of Thai tourism, the Thai government is carrying out Gastrodiplomacy using soft power, because typical Thai food is able to change the image of the country from sex tourism to culinary tourism. Gastrodiplomacy is part of public diplomacy and cultural diplomacy that uses food as a medium for cross-cultural communication. Thai gastrodiplomacy was officially issued in 2002 by the Thai government and was the first country to carry out gastrodiplomacy through the